Early effects of parathyroid hormone on vascularized bone regeneration and implant osseointegration in aged rats. (October 2018) - Jiang, Liting; Zhang, Wenjie; Wei, Li; Zhou, Qi; Yang, Guangzheng; Qian, Niandong; Tang, Yun; Gao, Yiming; Jiang, Xinquan
Abstract: The decreased bone mass and impaired osteogenesis capacities that occur with aging may influence the outcome of dental implants. Parathyroid hormone (PTH) (1–34) is an anabolic agent for the treatment of osteoporosis. However, little is known about its effects and mechanisms on vascularized bone regeneration and implant osseointegration in aging. In current study, we adopted both in vivo and in vitro approaches to explore the mechanisms of early actions of PTH (1–34) on the angiogenic and osteogenic microenvironment to enhance implant osseointegration in aged rats. Daily subcutaneous injections of 30 μg/kg PTH (1–34) were given to female rats aged 20 months beginning on next day of implantation and lasting for 5 weeks. Radiological and histological analysis confirmed that PTH (1–34) improved new bone formation, angiogenesis and implant osseointegration in aged rats in the early stage. The osteogenic potential of aged bone mesenchymal stem cells (BMSCs) was enhanced, while their adipogenesis capacity was attenuated. Furthermore, PTH (1–34) was shown to promote angiogenesis directly via endothelial cell migration and blood vessel formation in vitro. Meanwhile, PTH (1–34) stimulated more osteoclasts participation in bone remodeling by secreting angiogenic and osteogenic growth factors to induce early vascularization and stimulate the migration or differentiation of BMSCs indirectly. Together, these results demonstrate mechanistic insight into how PTH (1–34) regulates the angiogenic and osteogenic microenvironment to result in more active bone remodeling and new bone formation, making it an excellent potential therapeutic agent for rapid vascularized bone regeneration and implant osseointegration in the aged population.